Pengembangan Media Pembelajaran Audio-Visual Menggunakan Capcut pada Materi Fiksi Kelas VII SMP Negeri 1 Bawolato - Harefa, Agung Harapan; Ndruru, Mastawati; Halawa, Noibe; Riana, Riana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to develop digital-based audio-visual learning media using Capcut on fiction material for grade VII at SMP Negeri 1 Bawolato. The method used in this research is research and development (Research & Development) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data analysis technique used is quantitative descriptive. Based on the research results obtained, the developed learning media received a material expert validation result of 94.7%, language expert validation of 92%, and design expert validation of 95%. These percentages indicate that the digital-based audio-visual learning media using Capcut that was developed meets the feasibility criteria from the aspects of content, language, and design appearance. The practicality of the learning media was tested in two stages, namely a small group test (92.3%) and a field trial (88.2%).The effectiveness of learning media is measured by the completeness of student learning after using digital-based audio-visual learning media using Capcut. The results show a completeness rate of 100% in the small group trial, and 93.3% in the field trial. This proves that the digital-based audio-visual learning media using Capcut is effective, practical, and efficient for use in the learning process.